2022
DOI: 10.1108/srj-04-2021-0151
|View full text |Cite
|
Sign up to set email alerts
|

Women on boards, firms’ competitive advantage and its effect on ESG disclosure in Malaysia

Abstract: Purpose The purpose of this paper is to investigate the effects of women on board moderated by firms’ competitive advantage on firms’ environmental, social and governance (ESG) disclosures. Design/methodology/approach The sample consists of 332 firm-year observations from the year 2012 to 2017 of 65 firms listed in Bursa Malaysia. To improve the robustness of this analysis, the authors adopt clustering techniques in the regression analysis. Sensitivity analysis is also conducted using two-stage least square … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Several studies on the various board characteristics as determinants of ESGD have been identified. Board gender diversity and board independence have been consistently proven to have a positive impact on ESGD (Arayssi et al, 2020; Chebbi & Ammer, 2022; De Masi et al, 2021; Ellili, 2023; Gurol & Lagasio, 2023; Lavin & Montecinos‐Pearce, 2021b; Ozcan, 2019; Wan Mohammad et al, 2023). However, there were contrary findings where board gender diversity (Husted & de Sousa‐Filho, 2019; Ismail & Latiff, 2019) and board independence (Ismail & Latiff, 2019) negatively impact ESGD.…”
Section: Results and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on the various board characteristics as determinants of ESGD have been identified. Board gender diversity and board independence have been consistently proven to have a positive impact on ESGD (Arayssi et al, 2020; Chebbi & Ammer, 2022; De Masi et al, 2021; Ellili, 2023; Gurol & Lagasio, 2023; Lavin & Montecinos‐Pearce, 2021b; Ozcan, 2019; Wan Mohammad et al, 2023). However, there were contrary findings where board gender diversity (Husted & de Sousa‐Filho, 2019; Ismail & Latiff, 2019) and board independence (Ismail & Latiff, 2019) negatively impact ESGD.…”
Section: Results and Findingsmentioning
confidence: 99%
“…At the country level, reporting regulations (Lokuwaduge & Heenetigala, 2017) and stock exchange membership (Weber, 2014) have a positive influence on ESGD, whereas democracy and political stability negatively impact ESG performance (Mooneeapen et al, 2022). Huang et al (2022) Board gender diversity and board independence have been consistently proven to have a positive impact on ESGD (Arayssi et al, 2020;Chebbi & Ammer, 2022;De Masi et al, 2021;Ellili, 2023;Gurol & Lagasio, 2023;Lavin & Montecinos-Pearce, 2021b;Ozcan, 2019;Wan Mohammad et al, 2023). However, there were contrary findings where board gender diversity (Husted & de Sousa-Filho, 2019;Ismail & Latiff, 2019) and board independence (Ismail & Latiff, 2019) negatively impact ESGD.…”
Section: Determinants Of Esgdmentioning
confidence: 99%
“…The first method uses the STATA-based command xtscc, which calculates the standard error for panel regression with cross-sectional dependency using the Driscoll–Kraay estimator (Driscoll and Kraay, 1998). Following prior research (Le et al , 2020; Wan Mohammad et al , 2022), the method was selected because it is heteroskedasticity consistent, and the standard error estimates are robust to general forms of cross-sectional and temporal dependence, surpassing the shortcomings of traditional panel data statistical approaches (Hoechle, 2007). This study also provides a fixed-effects regression with a robust standard error for comparative analysis.…”
Section: Methodsmentioning
confidence: 99%
“…They further asserted that women tend to focus on issues related to social issues rather than environmental issues. Using psychological theory on gender, Wan Mohammad et al (2022) demonstrated that females on boards are unable to enhance ESG disclosures in smaller and competitively less advantaged Malaysian firms. Recent literature reviews have observed that the majority of gender diversity studies are underpinned by economic and management theories, such as agency theory, upper echelon theory, stakeholder theory, institutional theory and legitimacy theory (Banno et al , 2021; Campopiano et al , 2022).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%